2011
DOI: 10.1177/0748233711408381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E on reproductive hormones and testis structure in chronic dioxin-treated mice

Abstract: The purpose of this study was to investigate the effects of vitamin E on reproductive hormones and testis structure in mice treated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Five experimental groups of a combination of TCDD and vitamin E were designed as follows: 0 ng/kg/d and 0 mg/kg/d (control group), 100 ng/kg/d and 0 mg/kg/d (Group I), 100 ng/kg/d and 20 mg/kg/d (Group II), 100 ng/kg/d and 100 mg/kg/d (Group III), and 100 ng/kg/d and 500 mg/kg/d (Group IV) respectively. Vitamin E and TCDD were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
1
16
1
2
Order By: Relevance
“…VE supplementation resulted in remarkable restoration of the structural alterations in the testes as a result of CCl 4 treatment. This amelioration could be attributed to the capacity of VE to scavenge ROS and reduce the oxidative stress, as reported in the previous studies (41,42).…”
Section: Sperm Parametersmentioning
confidence: 57%
See 1 more Smart Citation
“…VE supplementation resulted in remarkable restoration of the structural alterations in the testes as a result of CCl 4 treatment. This amelioration could be attributed to the capacity of VE to scavenge ROS and reduce the oxidative stress, as reported in the previous studies (41,42).…”
Section: Sperm Parametersmentioning
confidence: 57%
“…These results were in agreement with other studies having reported that VE stimulated LH and FSH release (17,24). In addition, VE antagonized the decline of LH and FSH, testosterone, and sperm number; and reduced testicular injury as a result of dioxin treatment (41).…”
Section: Sperm Parametersmentioning
confidence: 99%
“…The decline in the testosterone concentration in the present study could be attributed to the decrease in 3b-HSD and 17b-HSD activities, diminution in pituitary LH synthesis and secretion as well as decreased prolactin concentration in EGEE-treated rats. Vitamin E protected against prolactin decrease in aroclor exposed rats (Murugesan et al, 2005a) and ameliorated 2,3,7,8-tetrachlorodibenzop-dioxin-induced decline of LH and testosterone concentrations in rats (Yin et al, 2012). The significant reversal to near normalcy observed in the activities of steroidogenic enzymes and in the concentrations of LH, prolactin and testosterone in rats co-treated with kolaviron or vitamin E indicates its chemoprevention against EGEE adverse effect on Leydig cells in the interstitial tissues and pituitary gland.…”
Section: Discussionmentioning
confidence: 86%
“…Inhibition of complex 1 is known to disrupt mitochondrial respiration and stimulates the mitochondrial production of ROS. In addition, vitamin E is known to maintain the structural integrity of sperm [68,69]. Vitamin C is known to protect mitochondrial DNA against oxidative damage [67].…”
Section: Discussionmentioning
confidence: 99%